Using applied mathematical models for business transformation - Trad, Antoine, 1963- (Advances in business information systems and analytics (ABISA) book series., 2020)
"This book examines the implementation of an applied mathematical model in business transformation projects, business engineering, and enterprise architecture research projects"--